Critical success factors of public-private partnership from 2000 to 2019: A literature review - Lydia Natalia; Nanny Dewi Tanzil; Prima Yusi Sari (Program Magister Ilmu Ekonomi Pascasarjana Universitas Jambi, 2021)
Public-Private Partnership (PPP) is one of the schemes that have inspired many countries in infrastructure development. One of the most discussed PPP topics by researchers is the concept of Critical Success Factors (CSF). Therefore, this study examines CSF publications for PPP projects from selected journal sites from 2000-2019. The results showed that research on CSF in PPP began to increase in 2012. The most identified CSFs were appropriate risk allocation and sharing, competitive and transparent procurement processes, favorable and efficient legal frameworks, commitment and responsibility of the public and private sectors, and a robust and reliable private consortium. Furthermore, it was also found that most countries that were the objects of research on PPP CSF were China, followed by Hong Kong and Australia. The results also show that the dominant research focuses on multi-sector types of infrastructure where CSF can be applied to all infrastructure sectors. The findings obtained in this study can provide an overview of CSFs for projects with PPP schemes in the future. Besides, the identified CSFs can be applied to any PPP infrastructure sector. They can assist stakeholders in increasing the likelihood of PPP project success and can be adopted for further research